2011
DOI: 10.1039/c0dt01042a
|View full text |Cite
|
Sign up to set email alerts
|

Density functional modelling of silicate and aluminosilicate dimerisation solution chemistry

Abstract: Common throughout sol-gel chemistry, including zeolite synthesis, aluminosilicate glass formation and geopolymerisation, is the process of inorganic oxide polymerisation and deprotonation. In this investigation, some of the fundamental reactions occurring during zeolite synthesis and geopolymerisation at high pH are investigated using density functional theory (DFT), and are compared with: (i) existing values reported in the literature, and (ii) new and previously published DFT-derived data for similar silicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
85
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 68 publications
(89 citation statements)
references
References 34 publications
4
85
0
Order By: Relevance
“…Such condensation between aluminosilicates is expected, as the formation of Si–O–Al bonds is thermodynamically more favorable than formation of Si–O–Si bonds . White et al . found thermodynamics of reactions involving aluminate monomer depend on charge state, but they did not provide results for reactions involving aluminosilicate reactants.…”
Section: Resultsmentioning
confidence: 99%
“…Such condensation between aluminosilicates is expected, as the formation of Si–O–Al bonds is thermodynamically more favorable than formation of Si–O–Si bonds . White et al . found thermodynamics of reactions involving aluminate monomer depend on charge state, but they did not provide results for reactions involving aluminosilicate reactants.…”
Section: Resultsmentioning
confidence: 99%
“…White et al [29] indicated that zeolite synthesis is the process of inorganic oxide polymerization and deprotonation which depend greatly on the pH value using density functional theory (DFT). Lower pH value led to decreased solubility of amorphous silica in the silicate dimerisation reactions.…”
Section: Powder Xrdmentioning
confidence: 99%
“…Because Si(OH) 3 O -is the conjugate base of a weak acid, it is observed only in appreciable quantities above pH 12 [19,20], and the second deprotonation requires even more highly alkaline conditions. To validate the structures of different silicate monomer species, the Gibbs free energies were calculated for deprotonation reactions of silica monomers, and the results were compared with experimental and theoretical data reported in the literature in Table 3.…”
Section: Silica Speciesmentioning
confidence: 99%
“…Hydrolysis and deprotonation of the silicate monomer have been studied extensively [18][19][20]. At a pH below 2, which is the point of zero net charge of silica, protonation of silanols forms cationic species [Si(OH) n (OH 2 ) 4-n ] (4-n)+ (n < 4) [19].…”
Section: Silica Speciesmentioning
confidence: 99%